La Iglesia católica en las más recientes historiografías de México y Argentina. Religión, modernidad y secularización - Lida, Miranda (El Colegio de México, A.C., 2007)
During the last decades, historians have become increasingly interested in the Catholic Church, so that now we can find a great amount  of researchers devoted to the history of the Latin American church.  However, this would have been unimaginable  decades ago, because the Church was a topic dealt with exclusively by “confessional”  historians  belonging to the ecclesiastical institution. The development of ecclesiastical history as a relevant research field for professional  historians has many common traits in Mexico and Argentina, the two cases described in this paper, which offers a critical review of the most recent historiography on the Church produced in these two  countries. This analysis allows us to compare two historiographic trajectories with many common concerns, viewpoints, and problems.